The Effects of Profitability and Firm Size on Firm Value: The Mediating Role of Islamic Social Reporting in Jakarta Islamic Index 70 - Azura Cahyani Karim; Khairunnisa (Indonesian Journal of Taxation and Accounting, 2026)
Purpose – This study aims to examine the direct effects of profitability and firm size on firm value, alongside evaluating the mediating role of Islamic Social Reporting (ISR) within the context of Sharia compliant companies. Methods – A quantitative explanatory approach is employed, utilizing panel data regression (Random Effect Model) and the Sobel test. The sample comprises 32 companies consistently listed on the Jakarta Islamic Index 70 (JII70) from 2021 to 2024, resulting in 128 observations. Findings – Profitability exerts a positive influence on firm value, whereas firm size demonstrates a negative effect. ISR does not significantly impact firm value nor mediate the relationships between profitability, firm size, and firm value. Research implications – The findings suggest that firm value in this sample is more strongly associated with financial performance than with ISR disclosure. Furthermore, large asset size is negatively associated with firm value, suggesting that managers should emphasize efficient asset utilization rather than mere expansion. Originality – This study provides new empirical evidence from the JII70 index, demonstrating the limited statistical relevance of ISR as a signal for firm value within this specific sample and timeframe. The results contrast with prevailing assumptions regarding ethical investing, suggesting that market valuations in the post-pandemic recovery phase were more strongly associated with direct financial returns and operational agility rather than short-term ISR disclosures.